2018
DOI: 10.1002/cne.24566
|View full text |Cite
|
Sign up to set email alerts
|

Matrix‐free mass spectrometry imaging of mouse brain tissue sections on silicon nanopost arrays

Abstract: Mass spectrometry imaging (MSI) is capable of detection and identification of diverse classes of compounds in brain tissue sections, whereas simultaneously mapping their spatial distributions.Given the vast array of chemical components present in neurological systems, as well as the innate diversity within molecular classes, MSI platforms capable of detecting a wide array of species are useful for achieving a more comprehensive understanding of their biological roles and significance. Currently, matrix-assiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…It has been shown to provide ultra-trace sensitivity and the detection of a wide range of compounds and compound classes 3740 . Previous MSI experiments examining mouse brain tissue sections on NAPA revealed enhanced ionization efficiency for certain lipid classes, such as HexCers and PEs, when compared to MALDI 41 . This enhanced sensitivity for difficult-to-detect species in tissues offers the possibility of using NAPA-MS to complement MALDI-MS for studying the roles of neutral lipids and other lipid classes in biological processes and disease.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to provide ultra-trace sensitivity and the detection of a wide range of compounds and compound classes 3740 . Previous MSI experiments examining mouse brain tissue sections on NAPA revealed enhanced ionization efficiency for certain lipid classes, such as HexCers and PEs, when compared to MALDI 41 . This enhanced sensitivity for difficult-to-detect species in tissues offers the possibility of using NAPA-MS to complement MALDI-MS for studying the roles of neutral lipids and other lipid classes in biological processes and disease.…”
Section: Introductionmentioning
confidence: 99%
“…The complete tissue extraction protocol and UPLC‐MS/MS conditions have been previously described . Briefly, lipid extracts from intact mouse lung and human skin tissue samples were prepared and analyzed by data‐dependent UPLC‐MS/MS to help aid in the lipid assignments from MSI experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Silicon nanoposts arrays (NAPAs) are a highly uniform matrix‐free LDI platform shown to provide ultra‐trace sensitivity and broad molecular coverage . Furthermore, MSI of biological tissues on NAPA indicated that detection of certain lipid classes, e.g., hexosylceramides (HexCers) and phosphatidylethanolamines (PEs), was enhanced compared to MALDI . Here, we present NAPA as a matrix‐free LDI‐MSI platform offering enhanced ionization efficiency of neutral lipids, such as TGs, and demonstrate imaging applications for mouse lung and human skin tissue sections.…”
Section: Introductionmentioning
confidence: 99%
“…Glycerophospholipids, sphingolipids, and fatty acids were annotated and spatially profiled throughout the tissue sections (see Figure 3C). More recently, advantages of NAPA in MSI were demonstrated in comparative studies to MALDI imaging of various lipid classes in tissue sections from mouse brain, lung, normal human skin, and hidradenitis suppurativa‐affected human skin 61 . Compared to MALDI, NAPA provided significantly enhanced ionization for PEs, phosphatidylethanolamine‐plasmalogens, hexosylceramides, and TGs in these complex biological samples 61 …”
Section: Inorganic and Nanophotonic Platforms For Msi Based On Ldimentioning
confidence: 99%
“…Some of them, including desorption ionization on silicon (DIOS), 47 nanostructured indium tin oxide slides for surface‐assisted LDI, 48 nanowire‐assisted LDI, 49 silica plate imprinting LDI, 50 and LDI from laser‐engineered graphene paper and polydopamine‐coated AR surfaces, 44,51 have been utilized in a limited number of imaging applications. A few inorganic materials and substrates for LDI, in particular, AuNP and AgNP, 33,34,36,52‐55 nanostructure‐initiator mass spectrometry (NIMS), 30,56‐59 and nanophotonic ionization from silicon nanopost arrays (NAPAs), 60,61 have been more broadly explored for MSI.…”
Section: Introductionmentioning
confidence: 99%